2017
DOI: 10.3892/mmr.2017.7035
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic ventrolateral pre-optic nucleus neurons are involved in the mediation of the anesthetic hypnosis induced by propofol

Abstract: Intravenous anesthetics have been used clinically to induce unconsciousness for seventeen decades, however the mechanism of anesthetic-induced unconsciousness remains to be fully elucidated. It has previously been demonstrated that anesthetics exert sedative effects by acting on endogenous sleep-arousal circuits. However, few studies focus on the ventrolateral pre-optic (VLPO) to locus coeruleus (LC) sleep-arousal pathway. The present study aimed to investigate if VLPO is involved in unconsciousness induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…In addition, it contains diverse neuronal types, including cholinergic, glutamatergic, parvalbumin-positive (PV + ) GABAergic and somatostatin-positive (SOM + ) GABAergic neurons [15]. The cholinergic, glutamatergic and PV + GABAergic neurons are wakefulness-promoting neurons [16,17], while the SOM + GABAergic neurons are sleep-promoting neurons [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it contains diverse neuronal types, including cholinergic, glutamatergic, parvalbumin-positive (PV + ) GABAergic and somatostatin-positive (SOM + ) GABAergic neurons [15]. The cholinergic, glutamatergic and PV + GABAergic neurons are wakefulness-promoting neurons [16,17], while the SOM + GABAergic neurons are sleep-promoting neurons [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic Sensor : Glucose infusion into the VLPO region promotes NREM sleep [ 108 ]. Anesthesia : Activation of VLPO neurons [ 63 , 69 , 119 , 120 ]; Manipulation(s) of VLPO neurons alter anesthesia [ 63 , 69 , 134 ] or have no effect on anesthesia [ 16 , 52 ]. …”
Section: Discussionmentioning
confidence: 99%
“…Manipulation(s) of VLPO neurons alter anesthesia [ 63 , 69 , 134 ] or have no effect on anesthesia [ 16 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoflurane directly activates VLPO neurons in vitro , and propofol anesthesia or pentobarbital at a sedative dose significantly increases the expression of c-Fos in VLPO neurons [ 11 ]. Local administration of GABA receptor agonists in VLPO shortens the propofol-induced LORR and prolongs the RORR [ 12 ]. It has been observed that selective knockout of the vesicular GABA transporter gene ( vgat ) in the POA slowed the transition to sedation immediately after dexmedetomidine administration, but the mice were sedated 30 min after injection; this indicates that POA GABAergic neurons were necessary for the rapid induction of dexmedetomidine sedation but not sedative maintenance [ 13 ].…”
Section: Preoptic Areamentioning
confidence: 99%